Record linkage as a vital key player for the COVID-19 syndemic -- The call for legal harmonization to overcome research challenges - Doetsch, Julia Nadine; Kajantie, Eero; Dias, Vasco; Indredavik, Marit S.; Devold, Randi Kallar; Teixeira, Raquel; Reittu, Jarkko; Barros, Henrique (International Journal of Population Data Science, 2023)
Key messages: Chronicity and social context influence COVID-19 risk highlighting its syndemic dimension Record Linkage advances knowledge on COVID-19, associated chronic diseases, and social indicators Further harmonization of data protection requirements for scientific research may create multilevel public health measures As a multidimensional tool, it optimizes integrated strategies and fosters solidarity on Health in All Policies (HiAP)